Sharia Compliance And Intellectual Capital Toward Protability Of Islamic Commercial Banks In Indonesia - Ningrum, Rianti Agmarin; Umiyati, Umiyati (JPS (Jurnal Perbankan Syariah), 2024)
This study aims to analyze the effect of sharia compliance (SC) proxied by profit sharing ratio (PSR), zakat performance ratio (ZPR), Islamic income ratio (IsIR), directors-employees welfare ratio (DEWR), and intellectual capital (IC) on profitability (return on assets-ROA) of Islamic commercial banks (ICB) in Indonesia. The population of this study was 13 Islamic commercial banks in Indonesia registered with the Financial Services Authority (FSA). The sample was selected using purposive sampling, so 8 ICB were obtained for the study. The data source used is secondary data from each ICB in Indonesia's annual report for 2019-2023. Data analysis uses panel data regression with an analysis tool in the form of Eviews Version 12.0. The results of the study show that PSR positively affects ROA. ZPR and DEWR negatively affect ROA. However, IsIR and IC do not affect ROA. The implications of this study can complement existing theories and be a reference for further research. In practice, this research can be used as reference material for Islamic banking in optimizing performance, evaluating banking to create competitive advantage values, and identifying assessments in decision-making for the community.